Prognostic Value Of Vascular Invasion In Breast Tumours In She-Dogs (Pilot Study) - Kovalenko, Maksym; Коваленко, Максим Станіславович; Beliy, Dmitry Dmitrievich; Beliy, Dmitry; Beliy, D. D.; Bely, Dmitry Dmitrievich; Bely, Dmitry; Bely, D. D.; Bilyi, D. D.; Bilyi, D.; Belyi, D. D.; Bilyi, Dmytro; et al. (Поліський нац. ун-т, 2021)
Breast tumours are the most common neoplasm in intact she-dogs. However, breast tumours in she-dogs differ significantly in morphological features and biological behaviour, so the definition of prognostic factors is relevant. A study on tumour cell dissemination in breast tumours in she-dogs by migration of these cells into blood and lymphatic vessels depending on their histological characteristics and disease stage was conducted. The study of the problem was performed on the basis of the clinic of modern veterinary medicine “Best” in Zaporizhzhia. She-dogs with breast neoplasms of different ages and breeds were used as objects in the proven absence of signs of metastatic lesions of other organs and tissues, including lungs, abdominal organs and bones. The presence of cancer cells in the vessels was determined by the tumour clots formed by them, fixed to the endothelium. The study revealed the presence of angioinvasion regardless of the clinical stage of the tumour process. In this case, the dissemination of tumour cells by migration into lymphatic vessels was observed only in the second clinical stage of breast tumours. In patients with stage 1 breast cancer in the vast majority of cases (66.7% of patients) angioinvasion is registered in the micropapillary invasive carcinomas (ICD-O code 8507/2). Tumour cells in blood vessels were verified in simple cribriform carcinoma (ICD-O code 8201/3) in more than 80% of she-dogs with stage 3 breast cancer. In contrast to the above groups, in patients with stage 2 cancer, migration of tumour cells into both blood and lymphatic vessels was found. Most often the signs of angio- and lymphoinvasion were found in invasive carcinoma mixed type (ICD-O code 8562/3), tubulopapillary carcinoma (ICD-O code 8503/3), and tubular carcinoma (ICD-O code 8211/3) ‒ in 34.1% and 36.8%, 19.3% and 26.3%, 17.0% and 10.5% of cases, respectively. The obtained results allow predicting the probability of penetration of tumour cells into blood and lymphatic vessels with a high degree of reliability, which in the future can better predict the biological behaviour of breast tumours. Пухлини молочної залози є найпоширенішим новоутворенням у інтактних собак. Однак пухлини молочної залози у собак істотно відрізняються за морфологічними ознаками та біологічною поведінкою, тому визначення прогностичних факторів є актуальним. Проведено дослідження дисемінації пухлинних клітин у пухлинах молочної залози у собак шляхом міграції цих клітин у кровоносні та лімфатичні судини залежно від їх гістологічних характеристик та стадії захворювання. Вивчення проблеми проводилося на базі клініки сучасної ветеринарної медицини «Бест» у Запоріжжі. В якості об’єктів використовували собак з новоутвореннями грудей різного віку та порід при доведеній відсутності ознак метастатичного ураження інших органів і тканин, у тому числі легень, органів черевної порожнини та кісток. Наявність ракових клітин в судинах визначали за утвореними ними згустками пухлини, фіксується до ендотелію. Дослідження виявило наявність ангіоінвазії незалежно від клінічної стадії пухлинного процесу. У цьому випадку дисемінація пухлинних клітин шляхом міграції в лімфатичні судини спостерігалася лише на другій клінічній стадії пухлин молочної залози. У хворих на рак молочної залози 1 стадії в переважній більшості (66,7% хворих) ангіоінвазія реєструється в мікропапілярних інвазивних карциномах (код МКБ-О 8507/2). Пухлинні клітини в кровоносних судинах були перевірені в простій крибриформній карциномі (код за МКБ-О 8201/3) у більш ніж 80% собак з раком молочної залози 3 стадії. На відміну від вищезазначених груп, у хворих на рак 2 стадії виявлено міграцію пухлинних клітин як у кровоносні, так і в лімфатичні судини. Найчастіше ознаки ангіо- та лімфоінвазії виявляли при інвазивній карциномі змішаного типу (код МКБ-О 8562/3), тубулопапілярній карциномі (код МКБ-О 8503/3) та тубулярній карциномі (код МКБ-О 8211/3). ‒ у 34,1% та 36,8%, 19,3% та 26,3%, 17,0% та 10,5% випадків відповідно. Отримані результати дозволяють з високим ступенем достовірності спрогнозувати ймовірність проникнення пухлинних клітин у кровоносні та лімфатичні судини, що в майбутньому може краще прогнозувати біологічну поведінку пухлин молочної залози.
Прогностичне значення судинної інвазії за пухлин молочної залози у сук (пілотне дослідження)
Білий Дмитро Дмитрович https://orcid.org/0000-0003-3896-0384
Keywords: metastasis; метастази; dogs; собаки; neoplasia; новоутворення; breast; молочна залоза